THE EXPLOITATION OF POVERTY IN THE VIRTUAL ERA AS AN IDEA FOR CREATING PAINTINGS - Gultom, Yusnita Maria Magdalena; Budiarta, I Dewa Putu Gede; Tjokropramono, I Gede Yosef (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
The exploitation of poverty that occurs in the virtual space of social media is an act of dehumanization of digital culture. The condition of the poor people who are less empowered is used as a weapon to gain wealth and popularity through various social media content. This painting is intended to describe the meaning, stages, and visual results with the theme of the phenomenon of poverty exploitation in the virtual era. The creator uses a creation method that broadly refers to the creation method discovered by Hawkins, consisting of three stages, namely exploration, improvisation, and forming. The characteristics of the six works created are seen in the use of thick textures, anatomically deformed objects, and colors that tend to be contrasting, unique, spontaneous, and simple in order to display an emotional and dynamic impression. The visualization of the work applies a variety of techniques, such as the wet-on-wet technique, the paint-melting technique, and the plaque technique. Through this work, it is hoped that all people, especially the lower middle class, will gain equality and be appreciated for their existence, both in social and cultural activities. In addition, the creator also persuasively invites the public to use social media wisely and creatively through the art of painting.